Response of with yam to different planting densities and trellis height - Tamara Morelos, Ricardo Enrique (2021)
The white yam tubers constitute one of the main food sustenance of producers in the Colombian Caribbean region, however, crop productivity is low due to the scarce use of sustainable management practices that contribute to the improvement of the crop. In this sense, a study was carried out at the Turipaná de Agrosavia Research Center, campus the Carmen de Bolívar headquarters with the objective of evaluate the yield response of white yam cv. Purple stem at different planting densities and trellis height. Six treatments were evaluated in a randomized complete block experimental design with arrangement in split-plot design, the main plot corresponded to two densities (14.285 plants ha-1 and 20.000 plants ha-1) and the subplots at three heights of trellises (1,6 m; 2,0 m and 2,4 m). The planting density was the only factor that significantly influenced the yield, the use of 20.000 plants ha-1 allowed an increase of 28.68% in the yield compared to the lower density. The use of supports with heights of 2,4 m in combination with one of the two planting densities induced the production of tubers not suitable for commercialization. The findings of this research suggest that increasing plant density could be a safe measure to increase the yields and economic efficiency of white yam crop. Future evaluations are required regarding the height of supports and number of plants to tie for each support.